DASHBOARD MANAGEMENT PENJUALAN DAN PEMBELIAN PADA TANGKAHAN IKAN - Arina Prima Silalahi; Harlen Gilbert Simanullang (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2018)
Technology has an important role in the implementation of human activities at this time, including in business activities. Today's technology is widely used to manage business activities with various forms of display/templates that are easy to use.Dashboards are used to display data concisely. Reports can be viewed quickly through a summary of the data displayed on the dashboard. So much data processing makes business activities that still carry out manual recording and see the report data sequence is felt to be less effective. Utilization of technology is highly needed by owners of small businesses when facing business management constraints such as a long time to manage data, loss of sales data, purchases and reports recapitulation errors. Besides, the need for fast and accurate data and information access is also needed to support and monitor business management. Based on these problems, a solution is needed to manage the overall sales and purchasing data, and display reports quickly and accurately by carrying out a study entitled "Dashboard Management of Sales and Purchases of Fish in Fish Spots".